Methods underpinning national clinical guidelines for hypertension: describing the evidence shortfall - Eccles Martin; Beyer Fiona R; Cook Julia VF; Dickinson Heather O; Campbell Fiona; Mason James M (BMC, 2006)
Abstract Background To be useful, clinical practice guidelines need to be evidence based; otherwise they will not achieve the validity, reliability and credibility required for implementation. Methods This paper compares the methods used in gathering, analysing and linking of evidence to guideline recommendations in ten current hypertension guidelines. Results It found several guidelines had failed to implement methods of searching for the relevant literature, critical analysis and linking to recommendations that minimise the risk of bias in the interpretation of research evidence. The more rigorous guidelines showed discrepancies in recommendations and grading that reflected different approaches to the use of evidence in guideline development. Conclusion Clinical practice guidelines as a methodology are clearly still an evolving health care technology.